Fasilitasi Musyawarah Daerah VII Ikatan Cendekiawan Muslim se-Indonesia (ICMI) Organisasi Daerah Kabupaten Wonosobo - Muafani Muafani; Samsul Munir; Salis Irvan Fuadi; Ali Mu’tafi; Robingun Suyud El Syam; Niken Kencono Ungu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Indonesian Muslim Scholars Association (ICMI) is a community organization that is Islamic, Indonesian, cultural, scientific, and intellectual. ICMI aspires to realize a moral and competitive civil society life order, so that it is prosperous outwardly and mentally. This research was motivated by the curiosity of researchers to find out the contribution of ICMI Wonosobo Regency to the lives of Muslims in Wonosobo. This paper is a qualitative field research, and is analyzed excitively. Conducted on Thursday, November 23, 2023 in Wonosobo Regency, with the object of research ICMI Regional Deliberation VII Wonosobo Regency Regional Organization, and the research subjects consisted of the activity committee, ICMI Wonosobo regency administrators, and several organizations, which involved 27 responses. The results of this activity show that the existence of the Indonesian Muslim Scholars Association (ICMI) in Wonosobo Regency implicitly has an impact on the community through inspiration. The idea emerged from the Indonesian Muslim Scholars Association in Wonosobo Regency to be able to advance Muslims themselves. The real impact can be proven by the large number of cadres of the Association of Scholars who enter the government bureaucracy with expertise in their respective fields. The conclusion focuses on the importance of the Indonesian Association of Muslim Scholars and its contribution and implications for the expansion of community empowerment in the social domain of the community. This research contributes to more specific future research directions and their contribution to sustainable human resource development.